In silico and in vitro studies of thiosemicarbazone-indole hybrid compounds as potent α-glycosidase inhibitors. (April 2022) - Bakherad, Zohreh; Bakherad, Hamid; Sepehri, Saghi; Faramarzi, Mohammad Ali; Mahnam, Karim; Mojtabavi, Somayeh; Mahdavi, Mohammad
Abstract: It is essential to study α-glucosidase enzyme (EC 3.2.1.20) inhibitors because of their physiological role as well as their clinical relevance. In previous research, a novel series of thiosemicarbazone-indole hybrid compounds were synthesized and reported. In the current research, α-glucosidase inhibitory activity of the derivatives was evaluated and then in silico studies were carried out on screened compounds. All derivatives exhibited a magnificent α-glucosidase inhibitory activity (IC50 = 27.0 ± 1.0–97.4 ± 1.5 µM) toward the acarbose as reference drug (IC50 = 750.0 ± 1.5 µM). Compound 1i having phenyl ring at the thiosemicarbazone moiety and the trimethoxymethyl substituent at phenyl moiety of C2 position of indole ring was the most potent compound (IC50 = 27.0 ± 1.0 µM) among other compounds. A kinetic study of 1i revealed that is a competitive inhibitor against α-glucosidase. Moreover, the molecular docking studies established that screened derivatives interacted with the essential amino acids in the active site. Finally, based on the molecular dynamics simulations and free binding energy calculations, complexes 1d, 1i and 1k with α-glucosidase showed a good stability in the active site. Van der Waals and electrostatic interactions also exhibited the most contributions to the stability of these complexes. Moreover, all the screened compounds showed agreeable ADME properties for oral bio-availability, and good drug-likeness. Graphical Abstract: ga1 Highlights: Thiosemicarbazone-indole hybrid compounds exhibit an excellent α-glucosidase inhibitory activity. Kinetic study of 1i revealed that it is a competitive inhibitor against α-glucosidase. MD simulations have emphasized the opportunities to improve the binding.